ANALISIS PENGARUH PELAYANAN DAN CITRA TERHADAP KEINGINAN MASYARAKAT UNTUK MENGGUNAKAN JASA LAYANAN GADAI PADA PEGADAIAN SYARI’AH DI KOTA PONTIANAK - NINGRUM B21107027, DIAH RETNO (Jurnal Curvanomic, 2015)
Shariah-based economicdevelopmentinIndonesia isgrowing veryrapidly, while thebusiness entitythat applies the principlesof Shari'ahin the operationssuch asbankingShariah, Shariahinsurance, Shariahmutual funds, capitalmarketsandpawn shopsShari'ahshari'ah'ah. Whichbecamethe focus ofdiscussioninthis studyis thePawnshopPontianak CityShari'ahasstate-owned enterprisesthatarechannelingcreditto the publicon the basis ofthelienlawsbased onShariahprinciples. Servicesandimagebecamethe primaryvariablein this studywith the aimtodetermine the effect ofthese variablesonthecustomer's decisionto use the serviceslienonShariahPawnshopPontianak City. The methodology usedisthe typeandsourceof data, populationandsample, data collection methods, data analysis techniquesincludingmultiple regression analysis, the classical assumption, koefisisendetermination, t testand thepartialF testsimultaneously. The hypothesis ofthis studyis theserviceandthe image ofpawnshopsShari'ah, partiallypositive and significant impactoncustomerdecisions. WhilesimultaneousservicesandpawnshopsimageShari'ahpositive and significant impactonthecustomer's decisionto usepawnservicesinShariahPawnshopPontianak City. From the results of this study indicate that the quality of service and the image of pawnshops Shari'ah, partially and simultaneously have a positive and significant impact on the customer's decision to use the services of lien in Sharia Pawnshop Pontianak. Thus the hypothesis that service quality has positive influence on customer decisions, the image of Shariah Pawnshop positive effect on the customer's decision and mortgage services and image simultaneously Shari'ah positive effect on the customer's decision is received.